Hiding in Plain Sight: How a Fallow Forestry Supply Chain Remains Illegitimate in the Eyes of the State - Sears, R.R.; Cronkleton, P.; Miranda Ruiz, M.; Pérez Ojeda del Arco, M. (Frontiers Media, 2021)
On-farm timber production is an important subsistence and economic activity of smallholder farmers around the world. Farmer investment in wood production and the degree of formality in the sector depends on access to and conditions of the market, the nature of the regulatory frameworks that govern rights to and movement of timber, and access to financing. We evaluate the process of formalization of a thriving and adaptive existing supply chain for small-dimension lumber originating in the fallows of smallholder farmers in the Peruvian Amazon. Through field research over three years based in semi-structured interviews with diverse actors in the Amazon, we found that the supply chain for fallow timber is driven entirely by informal and some illegal transactions. A key reason for this is the lack of an appropriate regulatory mechanism by which producers can gain authorization to harvest and sell this timber. We identify conditions necessary to formalize this sector, and evaluate the degree to which these are met under several scenarios. We recommend that the state develop mechanisms that recognize property rights of long-term residents and establish a simple fallow forestry registration mechanism; and that local governments or non-governmental organizations adopt adaptive and collaborative approaches to support farmers and provide training, information and networking among actors. State recognition of and support for fallow forestry, coupled with producers organizing for collective action on processing and marketing their timber, could result in the formalization of a significant volume of timber, improvements in income security for rural people, and the development of local entrepreneurial activities.